IMPLEMENTASI PEMBUKUAN SEDERHANA PADA UMKM ANNA COLLECTION DI DESA PANGKALAN KECAMATAN PLERED KABUPATEN CIREBON - Budianto, Erwin; Dhea Parlina, Nurhana (Transpublika Publisher, 2021)
MSMEs, or Micro, Small, and Medium-Sized Enterprises, are a critical component of Indonesia's economy. Each year, the development of MSMEs in Indonesia accelerates, as seen by their increasing contribution to GDP and workforce absorption by the MSME sector. However, some MSMEs continue to be constrained by accounting issues that have not been well organized and planned, resulting in a different final profit and loss value in accordance with the fact that there are issues with accounting financial management, which records each cash flow transaction in an organized and directed manner. MSME Anna Collection is one of the MSMEs with potential but has not yet developed. The Ana Collection MSME's bookkeeping is still unstructured and undirected, hence in the absence of a profit and loss statement for the business. It is believed that this community service activity would foster a knowledge for the critical nature of financial records in trading operations for MSMEs. Simple bookkeeping is critical in the business sector; there are numerous benefits to an MSME that maintains regular bookkeeping. Apart from serving as a benchmark for determining profits, the availability of bookkeeping enables business owners to ascertain their losses.